You can't always get what you want: change management in higher education. Issue 4 (2014) - ,
Abstract : Purpose – The purpose of this paper is to qualitatively describe an attempt to enhance curriculum design and delivery processes in universities through the development and introduction of new information systems and procedures.Design/methodology/approach – The author examines the experiences of five out of the total 27 institutions involved in the UK JISC Curriculum Design and Delivery programme as they attempted to implement campus‐wide changes.Findings – Common themes that emerged across all five projects were the interconnectedness of university systems, proliferation of alternative "feral" systems, a tendency for project remits to drift, resistance from other parts of the institution, planning imperatives, staff turnover and dependency failures. Conclusions are that cultural change underpins effective innovation and that cultural change is harder than technical innovation.Practical implications – Change is best achieved through participatory, campus‐wide approaches, although a "submarine" strategy may be necessary to deflect opposition. Stakeholders should be kept informed about benefits to them and it is important for projects to be responsive and adaptive and to recognize that participatory approaches may be institutionally risky. The paper concludes with practical recommendations for achieving lasting large‐scale change in the higher education environment.Originality/value – The JISC Curriculum Design and Delivery programme was arguably the largest single co‐ordinated Information and Communication Technology‐based change management programme yet seen in the UK and the findings of this study provide insights into common barriers to effective change in universities and how to overcome them. Acknowledgements : The projects described here were funded by the JISC Curriculum Design programme. Thanks are due to the JISC programme and support teams and to institutional project team members who contributed ideas that are reported on here, in particular Paul Bartholomew, Rebecca Freeman, Oliver Jenkins (Birmingham City University); John Norman, Amyas Philips, Harriet Truscott (Cambridge University); Pam Parker, Susannah Quinsee (City University London); and Stephen Griffiths, Andy Lloyd, Georgia Slade (Cardiff University).